An integrated system wide reactive power management strategy for transmission and distribution system based on techno economic analysis - Tang J.H.; Tengau M.; Busrah A.B.M.; Daud M.H.B.M.; Chong L.C.; Abdullah K.B. (Universiti Putra Malaysia Press, 2023)
This paper presents a methodology to determine the economic power factor at the point of power transfer between transmission and distribution (T & D) system for a vertically integrated utility company. An integrated reactive power management strategy is developed to optimize the planting up of reactive power compensation devices in the transmission and distribution system. The transmission and distribution network is modelled and simulated using commercially available software to analyse the transmission network losses, capacity released and voltage stability due to capacitor plant up. Economic analysis on the total cost of ownership of capacitor banks is used to determine the economic benefits of technical losses reduction and capacity. released in transmission and distribution equipment through the planting up of capacitor bank. The proposed methodology can be used by a vertically integrated power utility where a single utility own both the transmission and distribution system. A software base data analytic, power system automation and economic analysis tool was developed to facilitate the planning engineer in reactive power planning and management. 2017 Universiti Putra Malaysia Press.